The Highly Conserved MraZ Protein Is a Transcriptional Regulator in Escherichia coli - Eraso, Jesus M. (American Society for Microbiology, 2014)
The mraZ and mraW genes are highly conserved in bacteria, both in sequence and in their position at the head of the division and cell wall (dcw) gene cluster. Located directly upstream of the mraZ gene, the P(mra) promoter drives the transcription of mraZ and mraW, as well as many essential cell division and cell wall genes, but no regulator of P(mra) has been found to date. Although MraZ has structural similarity to the AbrB transition state regulator and the MazE antitoxin and MraW is known to methylate the 16S rRNA, mraZ and mraW null mutants have no detectable phenotypes. Here we show that overproduction of Escherichia coli MraZ inhibited cell division and was lethal in rich medium at high induction levels and in minimal medium at low induction levels. Co-overproduction of MraW suppressed MraZ toxicity, and loss of MraW enhanced MraZ toxicity, suggesting that MraZ and MraW have antagonistic functions. MraZ-green fluorescent protein localized to the nucleoid, suggesting that it binds DNA. Consistent with this idea, purified MraZ directly bound a region of DNA containing three direct repeats between P(mra) and the mraZ gene. Excess MraZ reduced the expression of an mraZ-lacZ reporter, suggesting that MraZ acts as a repressor of P(mra), whereas a DNA-binding mutant form of MraZ failed to repress expression. Transcriptome sequencing (RNA-seq) analysis suggested that MraZ also regulates the expression of genes outside the dcw cluster. In support of this, purified MraZ could directly bind to a putative operator site upstream of mioC, one of the repressed genes identified by RNA-seq.